Prevalence and associated factors of polypharmacy among adult Saudi medical outpatients at a tertiary care center - Salih Bin Salih; Muhammad Yousuf; Huda Durihim; Hind Almodaimegh; Hani Tamim (Wolters Kluwer Medknow Publications, 2013)
Objective: The objective of this study was to assess the prevalence of polypharmacy (PP) and the associated factors in medical outpatients. Materials and Methods: A cross-sectional, observational, descriptive study was carried out in adult medical outpatients attending internal medicine clinics at King Abdulaziz Medical City, Riyadh, Saudi Arabia from 1 March 2009 to 31 December 2009. PP was defined as the concomitant use of ≥5 medications daily. The number of medications being currently taken by patient was recorded. Effect of patients' age, gender, educational level, number of prescribers, disease load and disease type on PP was assessed by multivariate analysis using Statistical Package for Social Sciences Incorporated (SPSS Inc) Version 18. Results: Out of 766 patients included in the study, 683 (89%) had PP. The mean number of prescribed medications, oral pills and doses was 8.8, 9.6 and 12.1, respectively. Factors significantly associated with PP included age (≥61 years), disease load and the number of prescribers. Gender had no impact on PP while education beyond primary education significantly decreased PP. Hypertension, diabetes mellitus and dyslipidemia alone and as a cluster increased PP. Conclusion: We found an extremely high level of PP in medical outpatients at our tertiary care center. The impact of PP on medication compliance and control of underlying diseases in Saudi Arabia is unknown and needs to be studied at different levels of care.